Perselingkuhan Politik Ammatoa:Kajian Antropologi Politik Di Kajang, Bulukumba - Ilham A Hamudy, Moh (Unisia, 2012)
Kajang community is one of traditional communities in South Sulawesi. The community, led by Ammatoa, has philosophy of life in the form of oral narrative called as pasang ri Kajang (holy messages from Kajang), inherited from generation to generation. In daily life the community members strongly hold pasang ri Kajang, and consider it as the teaching of their ancestors. However, the tradition and values of pasang ri Kajang have changed. This is seen from the fact that many Kajang people frequently show deviant behavior, including lying, nepotism, stabbing from the back, short cutting, and ‘deceitful’. Political intrigue, patronclient, fraudulent, and political deceitful conducts between Ammatoa and ‘Pak Dewan’ have strengthened the above fact. As a consequence, pasang ri Kajang has not been considered as rules existing in the plural values of Kajang community. The elements of pasang ri Kajang have sunk in the complexity of modernization, and in the politization of Kajang elites. This further leads to the presumption that the tradition of Kajang people cannot be used anymore to answer challenges from new values that are relevant and rationale. Keywords: Kajang community, Ammatoa, pasang ri Kajang, deviant behavior, deceitful.